PROFIL SEROLOGI MYASTHENIA GRAVIS: TINJAUAN ATAS TIPE, KARAKTERISTIK, DAN RELEVANSI KLINIS AUTOANTIBODI - Asmedi, Ahmad; Bayuangga, Halwan Fuad (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Myasthenia gravis (MG) is an autoimmune disorder of the neuromuscular junction characterized by muscle weakness and fatigability. Understanding the serological profile of MG is key to accurate diagnosis and management. This literature review discusses the types and characteristics of autoantibodies in MG and their clinical relevance. Autoantibodies against the acetylcholine receptor (Anti-AChR) are the most common, found in the majority of generalized MG cases, and their pathogenesis involves antigenic modulation, ligand blockade, and complement activation. This subtype has a strong correlation with thymic abnormalities such as hyperplasia and thymoma. Autoantibodies against MuSK and LRP4 define other MG subtypes with distinct clinical phenotype, MuSK-MG often presents with severe bulbar symptoms, while LRP4-MG tends to be milder. A recommended diagnostic approach is algorithmic, starting with Anti-AChR testing, followed by Anti-MuSK and Anti-LRP4 in seronegative cases. Mapping this serological profile enables neurologists to achieve a precise diagnosis, predict disease course, and determine personalized therapy strategies, including the choice of immunomodulators and evaluation for thymectomy. Thus, serological classification has become the foundation of a precision neurology approach in managing myasthenia gravis. Keywords: Anti-AChR, Anti-LRP4, Anti-MuSK, Myasthenia gravis, Thymoma